Effect of Noise Sensitivity on Mental Health: Mediating Role of Sleep Problems - Yuyang Chen; Siyao Zheng; Yuting Liu; Andrew Smith; Jialin Fan (Noise and Health)
Objective Noise sensitivity refers to an individual’s general perception toward noise and may be associated with mental health and sleep. However, the effect of noise sensitivity on mental health requires further exploration. This study aimed to investigate the impact of noise sensitivity on mental health and the mediating role of sleep problems. Methods: We assessed 268 students from Shenzhen University, situated within 800 m of a construction site. We used the Weinstein Noise Sensitivity Scale-8, Patient Health Questionnaire-4, and Jenkins Sleep Scale-4 to assess noise sensitivity, depression, anxiety, and sleep quality. Results: Noise sensitivity was significantly and positively associated with anxiety, depression, and sleep problems (P < 0.01). Logistic regressions indicated that noise sensitivity positively predicted sleep problems (P = 0.011), anxiety, and depression (P = 0.014). The indirect effect of noise sensitivity on anxiety and depression through sleep problems accounted for 38.89% of the total effect (P = 0.268). Conclusion: Sleep problems serve as a mediating variable in the relationship between noise sensitivity and depression and anxiety. Future studies should explore additional variables that mediate the effect of noise sensitivity on mental health.